Pengaruh Fakultas, IPK, dan Jenis Kelamin Terhadap Tingkat Literasi Keuangan Mahasiswa Institut STIAMI Jakarta - Andrayanti, Iin; Sofyan, Mohammad (JURNAL EKONOMI, MANAJEMEN, BISNIS, DAN SOSIAL (EMBISS), 2023)
This study aims to examine the influence of Faculty, GPA, and Gender on the level of financial literacy of students at the STIAMi Jakarta Institute of Social Sciences and Management. To obtain the required data, data collection in the form of a questionnaire was used. The respondents studied were 100 FIA and Non-FIA students. Data analysis technique with Binary Logistic Regression Analysis. Based on the results of the study, shows that the Faculty influences the level of financial literacy of students in the Faculty of Administrative Sciences, Institute of Social Sciences and Management, STIAMI, Jakarta. Students of the Faculty of Administrative Sciences have a better level of financial literacy compared to students other than the Faculty of Administrative Sciences. GPA does not affect the level of financial literacy of students in the Faculty of Administrative Sciences, STIAMI Institute of Social Sciences and Management, Jakarta. Students with GPA > 3.00 have a better level of financial literacy than students with GPA < 3.00. and gender does not affect the level of financial literacy of undergraduate students in the Faculty of Administrative Sciences (FIA) STIAMI Institute of Social Sciences and Management, Jakarta. A person’s ability and intelligence in managing his finances are not determined by his genderThis study aims to examine the influence of Faculty, GPA, and Gender on the level of financial literacy of students at the STIAMi Jakarta Institute of Social Sciences and Management. To obtain the required data, data collection in the form of a questionnaire was used. The respondents studied were 100 FIA and Non-FIA students. Data analysis technique with Binary Logistic Regression Analysis. Based on the results of the study, shows that the Faculty influences the level of financial literacy of students in the Faculty of Administrative Sciences, Institute of Social Sciences and Management, STIAMI, Jakarta. Students of the Faculty of Administrative Sciences have a better level of financial literacy compared to students other than the Faculty of Administrative Sciences. GPA does not affect the level of financial literacy of students in the Faculty of Administrative Sciences, STIAMI Institute of Social Sciences and Management, Jakarta. Students with GPA > 3.00 have a better level of financial literacy than students with GPA < 3.00. and gender does not affect the level of financial literacy of undergraduate students in the Faculty of Administrative Sciences (FIA) STIAMI Institute of Social Sciences and Management, Jakarta. A person’s ability and intelligence in managing his finances are not determined by his gender